Causing Ripples in Local Power Relations: The meso-level influence of a hyperlocal news website. (3rd June 2017) - Chen, Nien-Tsu Nancy; Ognyanova, Katherine; Zhang, Chi; Wang, Cynthia; Ball-Rokeach, Sandra J.; Parks, Michael
Abstract : Hyperlocal news operations have been considered a promising alternative to the shrinking legacy media for sustaining civic discourse and engagement in local communities. However, these operations' meso-level influence on civic engagement has not been widely investigated. Building upon the Media System Dependency theory, this article proposed an analytical framework for assessing such influence. This framework was applied to an ethnically diverse city as a case study, and 15 interviews with city officials and legacy media reporters helped elucidate the ways in which organizational actors might respond to the entry of a non-commercial, participatory local news website. The implications of these organizational responses for shifting the power–dependency relation between the local media and political systems were discussed, and the findings pointed to both promises and barriers in materializing the democratic potential of hyperlocal news websites while calling for more research across different community contexts.